Effect of the Feed Additive Fytera Start on Growth Performance and Stool Quality of Nursery Pigs Fed Nutritional and Pharmacological Copper and Zinc Diets - Ty H. Kim; Jason C. Woodworth; Mike D. Tokach; Joel M. DeRouchey; Robert D. Goodband; Jordan T. Gebhardt; Chris P. A. van de Ligt (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 340 barrows (DNA 200 × 400; initially 13.4 ± 0.17 lb BW) were used in a 38-d growth study to determine the effect of Fytera Start (Selko, Indianapolis, IN) in diets with or without pharmacological levels of Zn and Cu on growth performance and stool quality of nursery pigs. Fytera Start is a blend of botanical extracts that has recently been introduced for use in nursery pig diets. Pigs were weaned at approximately 21 d of age, randomly allotted to pens based on initial BW, and then allotted to 1 of 4 dietary treatments in a completely randomized design. There were 5 pigs per pen and 17 pens per treatment across two barns. Treatment diets were formulated in three dietary phases and fed from d 0 to 10, d 10 to 21, and d 21 to 38, respectively. Treatments were arranged in a 2 × 2 factorial with main effects of Fytera Start (none or 100 ppm) and nutritional vs. pharmacological levels of Zn and Cu. The nutritional mineral concentrations were 110 ppm Zn and 16.5 ppm Cu throughout phases 1 to 3. The pharmacological mineral concentrations were 3,000, 2,000, and 110 ppm Zn in phases 1, 2, and 3, respectively, combined with 250 ppm Cu throughout phases 1 to 3. To achieve expected levels of Zn and Cu in the diet, Zn from zinc oxide and Cu from copper sulfate were added. On d 0, there was an unintentional main effect of Fytera Start (P= 0.008) on BW. As a result, d 0 BW was used as a covariate for all other growth performance responses. From d 0 to 21 and d 0 to 38, there was a Fytera Start × Zn/Cu interaction on ADG and ADFI (P<0.05) in which the addition of Fytera Start resulted in a numeric increase in ADG and ADFI in pigs not fed pharmacological levels of Zn/Cu; however, in pigs fed pharmacological levels of Zn/Cu, the inclusion of Fytera Start resulted in a numeric reduction in ADG and ADFI. There was a tendency for a main effect of Zn/Cu level on overall feed efficiency (P<0.10) where pharmacological levels of Zn/Cu improved feed efficiency. For fecal dry matter, there was a Zn/Cu × day interaction (P= 0.001) in which there was no difference in fecal DM regardless of Zn/Cu level on d 10 (P>0.10), but pigs fed pharmacological levels of Zn/Cu had lower fecal DM (P<0.001) compared to those not fed pharmacological levels of Zn/Cu on d 21. There was a main effect of day resulting in increased fecal DM (P<0.001) on d 10 compared to d 21. There was a main effect of day on fecal score (P= 0.010) resulting in a lower frequency of softer feces at d 10 compared to d 21. The lower frequency of softer feces observed on d 10 is consistent with the higher fecal DM on d 10 compared to d 21. In summary, feeding pharmacological levels of Zn and Cu resulted in increased BW, ADG, and ADFI. The inclusion of Fytera Start numerically increased BW, ADG, and ADFI in pigs fed nutritional levels of Zn/Cu and numerically decreased BW, ADG, and ADFI in pigs fed pharmacological levels of Zn/Cu. There was no impact of Fytera Start or Zn and Cu level on fecal DM on d 10. However, feeding pharmacological levels of Zn and Cu resulted in lower fecal DM at d 21. Fecal DM was higher on d 10 compared to d 21, and fecal score was numerically lower on d 10 compared to d 21.
Keywords: copper; growth; phytogenics; nursery pigs; zinc